Optimasi Umur Pahat Pada Proses Pembubutan Baja ST 42 - Chendri Johan (Publikasi dan UKI Press UKI Toraja., 2020)
The high cutting speed (Vc) and the varying depth of cut (a) made the tool life decrease. Machining variables are very influential on the tool life, namely cutting speed (Vc) which has a contribution of 13.36%, and depth of cut (a) which has a contribution of 68.56% to the tool life. The correlation value between tool life and the machining process variable is very significant, with the correlation value between the predictors obtained by R = 0.999.